Internationalization impacts on team innovation in Lithuanian high-tech firms - Mindaugas Laužikas; Aistė Miliūtė; Mukhammad Khalili (Insights into Regional Development)
Given a well-established literature on internationalization processes and its main impacts on companies’ performance (Begeny, 2018; Bužavaitė et al., 2019), it is worth examining how internationalization affects companies, driven by innovation at three different levels (individual, team and organizational) which is anchored in three main pillars: effectiveness, creativity and efficiency. The first pillar is related to strategic decision-making and business intelligence (along with data collection and analysis; setting efficiency criteria, strategic goals and outputs, as well as the tactics for each criteria). The second pillar covers a set of internationalization-related aspects, such as creative ideas generation, marketing and communications strategies, HR and R&D culture, leadership and talent development; while the third pillar is liaised with monitoring and execution of innovative activities. In line with studies with regard to innovation processes (Szopik-Depczyńska, 2015; Gries et al., 2017; Von Schomberg and Blok, 2018), the present paper continues examining the innovation performance; however, the main focus is on team innovation performance or the ways of unlocking the internationalization potential within team innovation processes via a set of aspects, such as effective decision-making, creative and divergent thinking, and efficient execution in teams. In light of the emergence of modern technology, employees of Lithuanian high-tech companies were selected for a quantitative survey, while scrutinizing the liaison between team internationalization and innovation commercialization success. Having the primary quantitative data (related to internationalization level, creative thinking, innovation performance in high-tech respondents’ teams) collected and analysed, further on, the innovation performance improvement suggestions are provided for the leaders of high-tech international teams.